The implementation of financial planning and cost accounting instruments in startups - Markus Pfützenreuter (Junior Management Science (JUMS), 2023)
This master thesis examines the question of how financial planning and cost accounting instruments are implemented in startups depending on their development stages. For this purpose, eleven semi-structured interviews were conducted with executives of startups in different development stages and an external expert. The results of this study show that startups follow a uniform approach along the development stages when implementing financial planning. Regarding the implementation of the individual financial planning instruments and cost accounting, various implementation differences and development steps between the development stages were identified. These differences and development steps are related to the industry, company growth, and business model expansion of the startups. Overall, this master thesis provides new and valuable insights for startups and scientists. For startups, the results are indications for the implementation and expansion of financial planning and cost accounting. For the scientific community, the results of this thesis represent the first cross-stage investigation of the implementation of specific management control systems.
Keywords: 650; Startups; Financial planning; Cost accounting; Management control systems